Exchange Rate Regimes in Norway 1816-2016 - Ragna Alstadheim (Norges Bank, 2016)
An overview of exchange rate regimes in Norway since 1816 is provided in a table which is divided into five sections; corresponding to the parts of the Norwegian monetary history defined and discussed in Eitrheim, Klovland and Øksendal (2016). Measured by the frequency of formal regime changes, the two parts of history before World War I were the two most stable. Several years pass between each regime change, and nominal stability was first established and then maintained. Long lasting formal regime stability was due to the absence of large external shocks to the economy. It was also due to a modest expected role for economic policy during the periods of domestic economic stress that the country experienced. Wars and large terms of trade shocks, in addition to growing ambitions regarding policy contributions to domestic economic stability, resulted in more frequent formal regime changes during the next two parts of Norwegian monetary history, covering the period from 1914 to 1986. This period of time was also characterized by nominal volatility. Finally, the "long return" to monetary stability in the most recent period after 1986 has simultaneously represented a return to fewer formal regime changes.
hdl:11250/2506533
Keywords: 330